Facies Analysis and Reservoir Characterization Using Petrophysical Methods in the Interest Zone in the 'FAN' Field, Kutai Basin, East Kalimantan - Isfan Fajar Fathur Rahman; Wahju Krisna Hidajat; Reddy Setyawan; Yunita Meilany; Dhimas Aditya Nugraha (Journal of Applied Geology, 2022)
One of the most prospective oil and gas producing basins in Indonesia is Kutai Basin which is located in East Borneo. In Kutai Basin there is a natural resource potential in the form of gas which is quite abundant. This is due to the richness of the source rock aspect in the Kutai Basin which is dominated by coal. Besides coal, in the Kutai Basin there is also claystone with rich organic matter (organic shale) that has an important role as a prospective source rock. Therefore, a final project research was conducted in the Kutai Basin, East Kalimantan. The purpose of the research is to identifying the type and content of subsurface lithology and fluids, calculating petrophysical parameters, and making the facies distribution map at the research site in potential and prospective zone to produce hydrocarbons which is called the zones of interest. The research is focused on reservoir rocks at the research site because the hydrocarbons accumulated in the reservoir rocks itself. By focusing research on reservoir rocks, it will be able to describe the modelling and calculation results of petrophysical parameters using several analytical methods such as qualitative and quantitative analysis methods, electrofacies and parasequence analysis methods, stratigraphic correlation analysis methods, facies analysis methods and depositional environments, and facies map analysis methods. In addition, by focusing research on reservoir rocks, it can develop and increase the level of optimization of exploration and exploitation of drilling wells. Based on the analysis data, the research location is included in the transitional depositional environment, delta in particular with distributary channels and mouth bars facies and also it can be identified some lithology such as sandstone, claystone, coal, limestone, and organic claystone and there are fluids with gas and water types.